Electrochemical Reactions at Sacrificial Electrodes: Electrochemical Synthesis of Aluminium(III) Alkoxides and their Coordination Compounds - Singh, Baljit; Bala, Kanchan; Singh, Kishanpal; Singh, Sukhveer (JOURNAL OF ADVANCES IN CHEMISTRY, 2009)
Electrochemical reactions of methanol, ethanol, propan-l-ol, butan-1-ol, pentan-1-ol, hexan-1-ol, heptan-1-ol, octan-1-ol, nonan-1-ol and decan-1-ol (ROH) at sacrificial aluminium anode and inert platinum cathode in the presence of tetrabutylammonium chloride as a conductive additive and acetonitrile as solvent yield aluminium(III) alkoxides. On refluxing with ligand (L) {where L = 2,2’-bipyridyl and 1,10-phenanthroline} these alkoxides don’t form coordination compounds. However, the coordination compounds have been prepared by electrolyzing the solution of above alcohols in the presence of ligand (L) at aluminium anode. These products have been characterized by microanalysis, physical measurements and IR spectral studies.General formula conform to M(OR)3 and M(OR)3.L.{where M- Aluminium and L- ligand}.All these reactions proceed with high current efficiencies.